Padrões morfogeométricos de Anomalocardia flexuosa (Linnaeus, 1767) (Bivalvia: Veneridae) ao longo da costa brasileira - Brito, Lucas (2024)
Anomalocardia flexuosa is a shallow burrowing bivalve mollusc which can be found in different environments along the Brazilian coast, being socioeconomically relevant for various human communities. The shells of molluscs reflect the diversity of lifestyles they possess and various environmental factors can influence their shape. Quantitative approaches to biological forms such as geometric morphometrics introduce necessary mathematical and statistical rigor for the description and comparison of these forms. Samples of 100 adult individuals, with a length greater than or equal to 13.80mm from locations along the Brazilian coast had their soft tissues removed and the shells photographed at a fixed distance by a single observer. Fourteen points were marked based on easily recognizable shell features and represent hinge, adductor muscles, and the areas of the shield and lunule. The Generalized Procrustes Analysis (GPA) removes information on position, scale, and orientation, in order to analyze only variations related to shape. Based on this data matrix, analyses were carried out to compare the shape of the shell in relation to the size of the specimens, main changes within the populations (PCA) and changes considering all samples (CVA). The study analyzed 1872 individuals of A. flexuosa collected in 12 Brazilian states, with sizes varying between 13.81 and 36.29mm in length. The specimens of A. flexuosa from Bragança/PA were identified as the largest, while those from Icapuí/CE, Rio Tinto/PB, and Camocim/CE were the smallest. The ANOVA indicated that the shape of the shell changes significantly with the size of the individuals and between the samples. The PCA explained 60.78% of the variation in the shape of the shell, with notable changes in the posterior end and the edges of the shell. The CVA resulted in two main axes, showing overlap of the samples, but also dissimilarities that aid in the distinction of the groups. The most notable differences occurred in the region of the edge and the angulation of the dentition and the posterior adductor muscle, as well as changes in the points linked to the pallial sinus and the dentition. Differences in habitat and climate result in larger shells at the extremes of the distribution. The availability of resources can have direct control over adult body size. Body size is influenced by ecological and evolutionary trade-offs between growth, resource availability, reproduction, predation, longevity, and other factors, in addition to historical events. The analysis suggests that the variation in the shape of the shell may be influenced by environmental and genetic factors. The research concludes that geometric morphometrics is an effective tool for studying the variation in the shape and size of bivalve shells. The results showed significant differences in the shape of the shell along the distribution of the species on the Brazilian coast. The GPA and PCA allowed a detailed view of the variations in the shape of the shell. The morphometric geometrics methods used in this study proved to be an effective, accurate, and low-cost approach to studying the variation in the shape of the shell of A. flexuosa and can be extended to other populations of marine invertebrates, especially bivalves.